Lee Silverman Voice Treatment to Improve Speech in Parkinson’s Disease: A Systemic Review and Meta-Analysis - Tingting Pu; Min Huang; Xiangyu Kong; Meng Wang; Xiangling Chen; Xixi Feng; Changyou Wei; Xiechuan Weng; Fan Xu (Parkinson's Disease)
Background. Speech changes occur in the early stages of Parkinson’s disease (PD) and cause communication difficulties, leading to social isolation. Lee Silverman voice treatment (LSVT) is a speech therapy approach designed to improve patients’ language and voice capabilities. Objective. The effectiveness of the LSVT was compared with that of other speech interventions or no treatment to evaluate PD patients with dysarthria. Design. Systematic review with meta-analysis of randomized trials. Data Sources: PubMed, Embase, Cochrane Library, CNKI, and SinoMed library were searched from inception to December 2021 related to PD and LSVT. Method. Abstracts were screened and reviewed against the eligibility criteria (intervention group participants were PD assessed based on LSVT (LSVT Loud) and randomized control). Result. Ten randomized controlled trials were identified on speech symptoms in patients with PD. Compared with the respiratory therapy (RET) exercise, or no training group, a significant improvement was detected in the sound press level (SPL) after immediate treatment during the reading of vowel and rainbow passages and an increase in semitone standard deviation (STSD). Furthermore, the LSVT training significantly increased the participants’ scores on unified Parkinson’s disease rating scale (UPDRS-III) and speech intelligibility. Conclusion. This meta-analysis demonstrated the efficacy of LSVT in increasing vocal loudness and functional communication among individuals with PD. However, most studies included participants with mild-moderate PD. Thus, additional randomized controlled trials (RCTs) with large sample sizes are needed to validate the efficacy of LSVT in patients with different progressions of PD, including severe PD.